Phonological Acquisition of a Deaf Adolescent: A Case Study of 23 Year Old-Indonesian Man - Miransyah, Indri Octa; Hanifa, Dina; Tambunan, Anna Riana Suryanti; Lubis, Fauziah Khairani (Journal of English Language Teaching and Linguistics, 2021)
This study is designed to find out how Indonesian phonemes are performed and changed in the form of words and sentences spoken by deaf young people 23 years old. This investigation employs a methodology for case studies. The aim of the research is to realize improvements in the accompanying phonemes and phonemes that are difficult for deaf teenagers to pronounce in Indonesian phrases. A 23-year-old deaf individual was the data source (informant). Data provision through the observation and listening methods require skill, recording and note making. The data were analyzed using the approach and the methodology of comparing links. The results have revealed that inhibited consonant, shift consonant, vibrating consonant experienced inconsistent phoneme changes. This means that phonology acquisition in the deaf depends on the accompanying phoneme.